Thermophilic bacilli isolated from geothermal soils of Gandom Beryan in Lut desert, Iran and their identification based on phenotypic and phylogenetic approaches - Sharifi Alghabpoor, S. F. (ՀՀ ԳԱԱ հրատ.)
Two thermophilic bacilli strains isolated from geothermal soil samples collected from Gandom-Beryan in Lut desert, Iran, were identified based on phenotypic and phylogenetic approaches and designed as Bacillus sp. Iranian S1 and Bacillus sp. Iranian S2. Լութ անապատի (Իրան) Գանդոմ-Բերյան երկրաջերմային տեղամասի հողից մեկուսացվել են և ֆենոտիպական ու ֆիլոգենետիկական բնութագրերի հիման վրա նույնականացվել են թերմոֆիլ աերոբ էնդոսպոր առաջացնող բակտերիաների երկու շտամներ` Bacillus sp. Iranian S1 և Bacillus. sp. Iranian S2: Из почв участка Гандом-Берян пустыни Лут, Иран, изолированы и по фенотипическим и филогенетическим характеристикам идентифицированы два штамма аэробных термофильных эндоспорoобразуюших бактерий, обозначенных как Bacillus sp. Iranian S1 и Bacillus sp. Iranian S2.
Keywords: Biology; Microbiology